Occurrence of gastrointestinal parasites in feces of cats from the cities of São Paulo and Guarulhos - Ragozo, Alessandra Mara Alves; Muradian, Vanessa; Silva, Jean Carlos Ramos e; Caravieri, Renato; Amajoner, Vanny Rose; Magnabosco, Cristina; Gennari, Solange Maria (Brazilian Journal of Veterinary Research and Animal Science, 2002)
Fecal samples were collected from 138 cats with different sex and breeds captured from the streets of São Paulo and Guarulhos for the determination of gastrointestinal parasites infection. The animals were kept individually at Zoonosis Control Center at the cities of São Paulo (107 cats) and Guarulhos (31 cats). The feces were individually collected and examined by using sacarose solution flotation technique (d=1.203g/cm³). From the 138 samples, 80 (57.97%) were positive. Among the protozoa the most frequent agent was Cystoisospora felis in 36 cats (26.09%) followed by Cystoisospora rivolta in 34 cats (24.64%), Cryptosporidium parvum (1.45%) in two cats and Sarcocystis spp, in one cat (0.72%). Among the helminthes, Toxocara cati presented the high occurrence with 43 positive cats (31.16%), followed by Ancylostoma spp with 12 positive cats (8.70%) and Platynosomum fastosum in two cats (1.45%). Mixed infection were observed in 25 cats (18.12%) with T.cati and Cystoisospora spp. and T.cati and Ancylostoma spp, been the most common occurrence, both with 7.97% (11 samples) of occurrence.